Factors associated with the length of stay of deep neck abscess patients - Yanti, Lisa Apri; Lubis, Friska Meutia; Bahar, Erial; Ghanie, Abla (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: Deep neck abscess is an accumulation of pus in one or more potential spaces of the deep neck fascia. Complications of deep neck abscesses are considered as an emergency in the Ear Nose Throat–Head and Neck field. One determining factor of prognosis in deep neck abscess patients is the length of stay in the hospital.  Objective: To find out the factors associated with the hospital length of stay of deep neck abscess patients. Method: Observational research using a cross sectional design. Data collection was carried out using medical record data on 91 subjects diagnosed with deep neck abscess at Dr. Mohammad Hoesin Hospital Palembang from July 2018 to May 2021. Result: From the 91 samples studied, the average hospital length of stay for deep neck abscess patients was 11.26 days. The study found factors related to the length of stay in the hospital, namely comorbidities (p=0.005), location of the abscess (p=0.004), pus culture (p=0.003), and the number of deep-neck spaces involved (p=0.005). Linear regression found that the most significant factors on the hospital length of stay were the involvement of abscess in 2 or more deep neck spaces (p = 0.002) and the presence of comorbidities (p = 0.005). Conclusion: Abscess involvement in 2 deep neck spaces or more and the presence of comorbidities were the most influential factors associated with the hospital length of stay in deep-neck abscess patients.ABSTRAKLatar Belakang: Abses leher dalam adalah akumulasi pus pada satu atau lebih ruang potensial fasia leher dalam sebagai akibat penjalaran infeksi. Komplikasi abses leher dalam masih merupakan keadaan darurat di bidang THT-KL. Salah satu faktor penentu prognosis adalah lama rawat di rumah sakit. Banyak faktor yang dapat mempengaruhi lama rawat pasien abses leher dalam di rumah sakit. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan lama rawat pasien abses leher dalam di RSUP Dr. Mohammad Hoesin Palembang. Metode: Penelitian observasional yang menggunakan rancangan potong lintang. Pengumpulan data dilakukan dengan menggunakan data rekam medis pada 91 subjek dengan diagnosis abses leher dalam di RSUP Dr. Mohammad Hoesin Palembang periode Juli 2018 sampai dengan Mei 2021. Hasil: Dari 91 sampel yang dilakukan penelitian, rerata lama rawat di rumah sakit pada pasien abses leher dalam adalah 11,26 hari. Penelitian mendapatkan faktor yang berhubungan dengan lama rawat di rumah sakit yaitu komorbid (p=0,005), lokasi abses (p=0,004), kultur pus (p=0,003), dan jumlah ruang leher dalam yang terlibat (p=0,005). Dari uji regresi linier didapatkan faktor yang paling memengaruhi lama rawat di rumah sakit adalah keterlibatan abses ³ 2 ruang leher dalam (p=0,002) dan terdapat komorbid (p=0,005). Kesimpulan: Keterlibatan abses pada 2 ruang leher dalam atau lebih, dan terdapatnya komorbid adalah faktor yang paling berpengaruh terhadap lama rawat pasien abses leher dalam.